Computational Prediction of the Low‐Temperature Ferromagnetic Semiconducting 2D SiN Monolayer. Issue 3 (30th October 2019) - Tkachenko, Nikolay V.; Song, Bingyi; Steglenko, Dmitriy; Minyaev, Ruslan M.; Yang, Li-Ming; Boldyrev, Alexander I.
Abstract : Since the discovery of graphene, 2D materials have captured the minds of scientists because of their attractive and unique electronic properties. In particular, magnetic 2D materials have become a subject of extensive discussions today. Using density functional theory calculations, it is shown that 2D SiN sheet (built out of nonmetallic main group atoms) is a ferromagnetic semiconducting material with a magnetic moment 1 μB per unit cell and an indirect bandgap of 1.55 eV. Calculated phonon spectrum and conducted ab initio molecular dynamics simulation reveal thermal and dynamical stability of the designed material. It is shown that the ferromagnetic state is stable up to 20 K. Magnetism of silicon mononitride can be described by the presence of an unpaired electron located on silicon atoms. The semiconducting and ferromagnetic properties of SiN monolayer open many opportunities for its potential use in spintronic and nanoelectronic devices. Abstract : A novel silicon mononitride material is predicted. The SiN sheet is a ferromagnetic semiconductor with an indirect bandgap of 1.51 eV. Calculated phonon spectrum and conducted ab initio molecular dynamics simulation reveal thermal and dynamical stability of the designed material. The semiconducting and ferromagnetic properties of SiN sheet open many opportunities for its potential use in spintronic and nanoelectronic devices.